Serodiffusion of Helicobacter Pylori and HAV in Patients Attending Two Centers in Baghdad - AlKhori, Firas Elias; Saour, May Yousif; Ramadhan, Shatha (AL-Kindy College Medical Journal, 2013)
Background: Helicobacters are motile curved, oxidase and catalase positive, gram negative rods similar in morphology to vibrios. The cells have polar flagella and are often attached at their ends given pairs "S" shapes or seagull appearance. Object i ves: The present study was undertaken to estimate the serodiffusion of H. pylori and hepatitis A virus (HAV) in 300 patients attending two centers in Baghdad. Metthods:: HAV was determined by the detection of HAV-IgM in the serum samples. Detection of H. pylori was by ELISA and endoscopic examination. Resul t s: The serodiffusion of H. pylori was 40% (n=120). Out of the 120 patients infected with H. pylori, 50(41 .6%) patients were diagnosed clinically to have gastric antraum, the remaining 70 (58.4%) patients were apparently free of any disease. The present findings showed that the serodiffusion of anti hepatitis A virus (HAV) antibody was 30 % (n=90). Concllusiions:: This study shows relatively high serodiffusion of H. pylori and HAV in the studied group. None of the cases had co-infection with both H. pylori and HAV; this may be due to the small size number of the patients under study.